Entamoeba gingivalis in Acute Osteomyelitis of the Mandible - Feriyl Bhaijee; Diana Bell (Case Reports in Medicine)
An 86-year-old woman presented with osteonecrosis of the mandible following bisphosphonate therapy for multiple myeloma, and underwent surgical debridement and multiple dental extractions. Histopathologic examination of the necrotic bone fragments revealed acute osteomyelitis with mixed flora and organisms morphologically consistent with Entamoeba gingivalis. In addition to oral scrapings and sputum, E. gingivalis has been identified in specimens obtained from the uterus, cervix, neck lymph nodes, and lung. It is rarely found in lesions of the head and neck. We present an unusual case of E. gingivalis in acute osteomyelitis of the mandible, following bisphosphonate therapy for multiple myeloma. To our knowledge, this is the first reported case of E. gingivalis in association with osteomyelitis.